Differences in Children's Curiosity and Learning Motivation in Conventional Vs Experiential Learning Methods - Wedi Iswandi; Hendry (CONVERSE Journal Communication Science, 2025)
This study aims to examine the differences in students’ curiosity and learning motivation between those taught using conventional methods and those using experiential learning methods. The research employed a quasi-experimental design with a Pretest-Posttest Control Group Design. The participants consisted of 100 elementary school students, divided into two groups: the experimental group (experiential learning method) and the control group (conventional method), each with 50 students. Instruments used in this study included questionnaires measuring curiosity and learning motivation. Data were analyzed using independent t-tests. The results showed significant differences between the two groups. Students who received experiential learning showed a greater increase in both curiosity and learning motivation compared to those taught using conventional methods. Therefore, experiential learning is more effective in enhancing students’ curiosity and learning motivation at the elementary level